Improvement of the occupational risk management process in the work safety system of the enterprise - Oleg Bazaluk; Vitalii Tsopa; Małgorzata Okrasa; Artem Pavlychenko; Serhii Cheberiachko; Olena Yavorska; Oleg Deryugin; Vasyl Lozynskyi; Vasyl Lozynskyi (Frontiers in Public Health, 2024)
PurposeThe research purpose is to improve the management of occupational risks associated with hazards as well as the organization’s capabilities to identify hazardous factors (HFs) using the “BOW-TIE” method in accordance with the provisions of the ISO 45001:2019 standard.MethodsTo improve occupational risk management, the “BOW-TIE” method has been introduced into occupational health and safety management systems. This approach facilitates a comprehensive description and analysis of potential risk development from identifying hazardous factors to studying the consequences. It visually integrates fault and event trees to provide a holistic view of risk dynamics.ResultsThe improvement of the occupational hazard risk management process considers both internal and external factors affecting the organization, thereby increasing the probability and severity of potential hazardous events. The revised approach categorizes risk levels as acceptable, unacceptable, or verifiable. In addition, occupational risk management requires an in-depth analysis of the organization’s external and internal environment to identify hazards that affect the probability and severity of potential hazardous events.ConclusionThis research proposes an innovative approach to occupational risk management by determining the magnitude of occupational risk as the cumulative result of assessing risks associated with all external and internal factors influencing the probability of hazardous event occurring. The introduction of the “BOW-TIE” method, combined with a comprehensive analysis of the organizational environments, facilitates a more effective and nuanced approach to occupational risk management.